A young female case of acromegaly presenting with diabetic ketoacidosis - Maskey, R; Shakya, DR; Peeyush, D; Lavaju, P; Karki, P (Sunsari Technical College Journal, 2013)
Diabetes mellitus is reported to be common in cases with acromegaly. However, diabetic ketoacidosis (DKA) is rarely reported in this disease. Here is a 17 year old female case with acromegaly who presented to our hospital with the first presentation was DKA. DOI: http://dx.doi.org/10.3126/stcj.v1i1.8662 Sunsari Technical College Journal Vol.1(1) 2012 57-60